2017
DOI: 10.1371/journal.pone.0176622
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of CT perfusion in diagnosing acute ischemic stroke: A systematic review of 27 trials

Abstract: ObjectiveTo systematically evaluate and compare the diagnostic accuracy of CT perfusion (CTP), non-enhanced computed tomography (NCCT) and computed tomography angiography (CTA) in detecting acute ischemic stroke.MethodsWe searched seven databases and screened the reference lists of the included studies. The risk of bias in the study quality was assessed using QUADASII. We produced paired forest plots in RevMan to show the variation of the sensitivity and specificity estimates together with their 95% CI. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 39 publications
1
33
0
1
Order By: Relevance
“…Although the patient had severe multiple vascular occlusion, dizziness as well as headache was main clinical manifestations, considering the strong compensatory mechanism of cerebral vessels mainly [12][13][14][15]: the left ICA occlusion, M1 segment of left brain artery occlusion, anterior communicating artery are open, and the right ICA system compensates the left cerebral anterior artery and middle cerebral artery through anterior communicating artery. The meningeal branch of left anterior cerebral artery supplied blood to left middle cerebral artery, and the signal of left middle cerebral artery M2 segment was low.…”
Section: Discussionmentioning
confidence: 99%
“…Although the patient had severe multiple vascular occlusion, dizziness as well as headache was main clinical manifestations, considering the strong compensatory mechanism of cerebral vessels mainly [12][13][14][15]: the left ICA occlusion, M1 segment of left brain artery occlusion, anterior communicating artery are open, and the right ICA system compensates the left cerebral anterior artery and middle cerebral artery through anterior communicating artery. The meningeal branch of left anterior cerebral artery supplied blood to left middle cerebral artery, and the signal of left middle cerebral artery M2 segment was low.…”
Section: Discussionmentioning
confidence: 99%
“…Using the time to peak and mean transit times as surrogate measures of perfusion to identify the penumbra lack precision, as intracranial collateral blood flow pathways vary across individuals and brain regions. A recent systematic review incorporating more than 2000 patients across 27 studies was carried out to assess the diagnostic accuracy of CTP in acute ischemic stroke 38 . It concluded that more high quality evidence is required for CTP to be used as a diagnostic tool that can reliably inform on selection of stroke patients for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CT perfusion is more accurate at diagnosing acute ischaemic stroke than non-contrast CT alone, with two pooled analysis reporting high sensitivity (80%–82%) and very high specificity (95%–96%) for stroke 6 7. However, it is important also to be aware of its limitations in diagnosis.…”
Section: How Can Ct Perfusion Help Decision-making?mentioning
confidence: 99%
“…In one study, CT perfusion had a sensitivity of 62% in detecting diffusion-weighted MRI confirmed lacunar infarcts compared with just 19% for non-contrast CT 8. Sensitivity for posterior circulation infarcts is lower than for hemispheric cortical infarcts, but CT perfusion is more sensitive in diagnosing acute posterior circulation stroke than non-contrast CT, with reported sensitivity of 76% and specificity of 93% 6…”
Section: How Can Ct Perfusion Help Decision-making?mentioning
confidence: 99%
See 1 more Smart Citation